1978
DOI: 10.1021/ja00472a046
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical reactions in organized monolayer assemblies. 8. Environmental effects on photochemical reactions: contrasts in the photooxidation behavior of protoporphyrin IX in solution, monolayer films, organized monolayer assemblies, and micelles

Abstract: Die Photooxidation der Ester (I) des Protoporphyrins IX ergibt hauptsächlich die Hydroxyaldehyde (II) und die Dialdehyde (III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…The photoproduct fluorescence spectra that we observe are very similar to those recorded in 5-ALA-treated tissues (10)(11)(12)17,18). These have been suggested by Whitten and coworkers (15,16) as chlorin products because they appear to have the red Q band feature typical of a chlorin-type photoproduct. Previous studies (10)(11)(12)17,18) have shown that it is difficult to identify the exact nature of the photoproduct.…”
Section: Two-photon Spectroscopysupporting
confidence: 86%
See 1 more Smart Citation
“…The photoproduct fluorescence spectra that we observe are very similar to those recorded in 5-ALA-treated tissues (10)(11)(12)17,18). These have been suggested by Whitten and coworkers (15,16) as chlorin products because they appear to have the red Q band feature typical of a chlorin-type photoproduct. Previous studies (10)(11)(12)17,18) have shown that it is difficult to identify the exact nature of the photoproduct.…”
Section: Two-photon Spectroscopysupporting
confidence: 86%
“…Protoporphyrin IX is the sensitizer generated in situ when a specimen or subject has been administered its metabolic precursor, 5-ALA (9). The photochemical behavior of PpIX has been extensively documented (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and thus serves as an excellent test case for TPE-PDT. Furthermore, because the photochemical behavior of PpIX may depend on the mode of excitation, TPE studies may help to shed light on some of its photodynamic anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of PpIX, this result is qualitatively consistent with a finding published by Krieg and Whitten (2), who concluded that the detailed mechanism of PpIX bleaching in erythrocyte ghosts involved reaction of 1 O 2 with an intermediate oxidizable amino acid. An oxygen dependence to the rate of Photofrin bleaching is consistent with results reported by Spikes (5), although the extent of the role of 1 O 2 was not clear in that study, which was performed using a variety of model environments in fluid solution.…”
Section: Introductionsupporting
confidence: 88%
“…Photoconversion of PpIX into two chlorin-type hydroxyaldehyde isomers called 'photoprotoporphyrin' has been documented (9,19). Several porphyrin-type formyl derivatives are formed during phototransformation of PpIX (19,20). The photophysical properties of Ppp and its dimethyl ester in organic solutions and biological environments has been investigated by several groups (16,17,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…The environment of PpIX is of crucial importance for the photobleaching process (1,16,19,20,25,26). In organic solvents (methylene chloride, dimethylacetamide, acetone) the predominant photoproduct is the hydroxyaldehyde chlorin.…”
Section: Discussionmentioning
confidence: 99%